Peningkatan Keterampilan Pembuatan Konten Edukasi Digital Melalui Workshop Canva dan CapCut - Ferida Rahmawati; Emi Nurlaela; Arditya Prayogi; Imam Prayogo Pujiono; Ahmad Abdussalaam; Abdi Cahya Subekti (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
The rapid development of digital technology demands mastery of educational content creation skills for Madrasah Aliyah (Islamic Senior High School) students in the Industry 4.0 era. Initial observations at MA Salafiyah Simbangkulon indicated limitations among students in this regard. This community service activity aimed to enhance students' understanding and practical skills in using Canva and CapCut applications to create engaging and innovative educational content. This activity was implemented through a workshop using presentation, practicum, and discussion methods, involving 40 grade 10 students of MA Salafiyah Simbangkulon. The success of the activity was measured by comparing pre-test and post-test results. The results showed a significant improvement in students' conceptual understanding and practical skills in Canva and CapCut. This was evidenced by an average score increase of 68% on the post-test compared to the pre-test. Furthermore, students successfully created sample educational content using both applications. Based on these results, it is recommended that advanced training and integration of Information and Communication Technology (ICT) utilization in the madrasah curriculum are needed to support a more creative, participatory, and relevant learning process in line with contemporary demands.